Social Responsibility as a Cross-Cutting Axis of the University's Commitment to the University Community and Interest Groups - Pulido-Capurro, Víctor Manuel; Olivera-Carhuaz, Edith Soledad; Briceño-Vergel, Gissela; Acevedo-Flores, Jessica; Quiroz-Rosas, Juan (Journal of Sustainable Competitive Intelligence, 2025)
Objective: Analyze social responsibility as a cross-cutting axis of the University's fundamental commitment to the university community and interest groups. Method: A qualitative study at a descriptive, explanatory, and correlational level, based on a systematic literature review and regulatory analysis, integrating the principles of environmental education, sustainability, and the Sustainable Development Goals (SDGs). Results and Discussion: Scientific research and the generation of new knowledge allow us to evaluate the impact that the actions of the university community have on the environment; therefore, social intervention projects and sustainable campuses constitute indicators and criteria related to the principles and values ​​required for the construction of the paradigm of sustainable development and university social responsibility, which privileges efforts to serve the community and integral development. Originality/value: The study gathers information on the historical evolution of the concept of social responsibility up to the present moment, where regulations, sustainable development objectives and environmental education strengthen university social responsibility. Main Conclusion: USR is consolidated as a structuring policy of the contemporary university, articulating teaching, research, extension, and institutional management with a focus on sustainability and social transformation, thereby strengthening the university’s role as an agent of human and social development.